A Self-Determination Theory Perspective on the Success and Failure of Eating Regulation In Women: Does Planning and Self-Monitoring the Quality Versus the Quantity of Eating Matter? - Guertin, Camille (Université d'Ottawa / University of Ottawa, 2020)
Based within the Self-Determination Theory (SDT), the overall objective of this thesis was to examine how motivational processes involved in the regulation of eating give rise to different self-regulation strategies in terms of eating quality and quantity, and how the adoption of these strategies influence women’s eating behaviors and life satisfaction over time. This objective was achieved through a series of eight studies, divided into four manuscripts. First, a measure that would allow us to assess healthy and unhealthy eating behaviors based on recent recommendations of Canada’s Food Guide was developed and validated. In Manuscript #1, we validated the Healthy and Unhealthy Eating Behavior Scale (HUEBS) by examining the structure of the scale (Study 1 N = 360; Study 2 N = 711) and by establishing convergent validity through the examination of the relationships between motivational concepts, healthy and unhealthy eating behaviors as measured by the HUEBS, and waist circumference (Study 2 N = 711; Study 3 N = 264). Results supported the factor structure of the scale. It was also demonstrated that as women moved along stages of change for eating regulation, they reported higher levels of self-determined (versus non-self-determined) motivation and a higher consumption of healthy (versus unhealthy) foods. Furthermore, findings showed that healthy eating fully mediated the relationship between self-determined motivation and waist-circumference, and that the relationship between self-determined motivation and healthy eating was moderated by stages of change. Since there was also a need to develop a scale that would allow us to measure planning and self-monitoring strategies in terms of eating quality (i.e., nutrient intake) and quantity (i.e., calories and portion sizes), Manuscript #2 validated the Planning and Self-Monitoring the Quality and Quantity Scale (PMQQS; Study 1 N = 355; Study 2 N = 318). Results supported the 6-factor structure of the scale and demonstrated that strategies related to the quality of eating were more strongly and positively associated with healthy eating and more strongly and negatively associated with unhealthy eating, whereas strategies related to the quantity of eating were more strongly and positively associated with bulimic symptoms and Body Mass Index (BMI). Manuscript #3 then examined if the strategies assessed by the PMQQS provided additional variance to eating behaviors over and above the effects of motivation (Study 1 N = 456) and if the strategies mediated the relationships between motivation and eating, while controlling for BMI (Study 1 N = 456; Study 2 N = 979). Overall, it was found that strategies played a significant role in explaining eating behaviors and that planning and self-monitoring the quality of eating mediated the relationships between autonomous motivation and healthy and unhealthy eating, whereas planning and self-monitoring the quantity of eating mediated the relationship between controlled motivation and bulimic symptoms. Finally, in Manuscript #4, we tested a longitudinal model (N = 230) examining the roles of goals and motivation in the prediction of the strategies and various types of eating and the effects of adopting these behaviors on life satisfaction over a 3-month period. Results revealed that intrinsic goals were positively associated with autonomous motivation whereas extrinsic goals were positively associated with controlled motivation for eating regulation at Time 1 (the baseline), and that autonomous motivation positively predicted quality strategies whereas controlled motivation positively predicted quantity strategies at Time 2 (1 month). Planning and self-monitoring quality then predicted healthy and unhealthy eating behaviors, whereas planning and self-monitoring quantity predicted bulimic symptoms at Time 3 (3 months). Finally, healthy eating was positively associated with life satisfaction, whereas bulimic symptoms was negatively associated with life satisfaction at Time 3. Overall, this thesis increases knowledge on why some women succeed, whereas others fail, to regulate their eating behaviors over time.
Keywords: Self-Determination Theory; Eating Regulation; Self-Regulation Strategies; Quality and Quantity